From fundamental absence to absolute noth-ingness - Rošker, Jana S. (Asian studies, 2025)
This article aims to explore the existence of absolute Nothingness within the Daoist framework. The inquiry will revolve around an imagined dialogue, juxtaposing the ideas of Nishida Kitaro and Wang Bi through a contrastive analysis employing the transcultural method of sublation. While Nishida asserted that his philosophy was underpinned only by Zen Buddhism and Western philosophy, we will illuminate the frequently overlooked but profoundly influential role of Chinese Daoism in shaping Nishida's concept of nothingness. It is no coincidence that Nishida himself appeared to be unaware of this Daoist influence. I believe that this oversight constitutes a flaw not only in Nishida's work but also in its common reception. By comparing Nishida’s and Wang’s respective conceptualizations of a dynamic (or “moving”) present, I will demonstrate that both theories depict time in a similar way, i.e. as emerging from the intimate "translocation" of reality. Building on this foundation, this analysis critiques Nishida's reductionist view that the Chinese (or Daoist) concept of nothingness is confined to a mere opposition of being, representing a simplistic dichotomy between being and non-being. Instead, I argue that Wang Bi's notion of original nothingness or fundamental absence (benwu ??) offers a nuanced parallel to Nishida's concept of absolute nothingness (zettai mu ???).
Keywords: Daoist nothingness; daoistični nič; meontologija; Meontology; moving present; Nishida Kitaro; premikajoča se sedanjost; Wang Bi